Analysis of Blue Accounting Sustainability in Seaweed Cultivation from Economic, Social, and Environmental Perspectives (Study on: Seaweed Farmers In Banggai Regency, Central Sulawesi) - Suci Rahmadani Djamaludin; Uci Yuliati; Nurul Asfiah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Seaweed farming has become one of the primary livelihoods for coastal communities in Indonesia, particularly in Tanjung Tuwis Village, Banggai Regency, Central Sulawesi. Despite its potential, the sustainability of seaweed cultivation remains challenged by economic, social, and environmental issues. This study seeks to examine the sustainability of seaweed farming practices within the framework of Blue Accounting by addressing the problem of how cultivation activities contribute to the economic welfare of farmers, social dynamics of the community, and ecological impacts on coastal resources. The research aims to provide a comprehensive understanding of seaweed farming sustainability that can guide policymakers in the fisheries sector. Using a qualitative descriptive approach, data were collected through observations, semi-structured interviews, and focus group discussions with farmers, village officials, community leaders, and representatives from the Fisheries Service of Banggai Regency. Secondary data were obtained from academic literature, reports, and supporting documents. Data validation employed triangulation of sources, techniques, and time, while thematic analysis was conducted based on the Triple Bottom Line framework, covering economic (profit), social (people), and environmental (planet) aspects. The results reveal that seaweed farming significantly contributes to household income and local economic development, enhances social cohesion and institutional participation, but also poses challenges in environmental management, particularly related to waste, cultivation impacts, and conservation awareness. Overall, the study highlights the importance of integrating economic benefits with social empowerment and ecological preservation to achieve sustainable coastal resource management.